Severe Angle Class III skeletal malocclusion associated to mandibular prognathism: orthodontic-surgical treatment - Marcelo Quiroga Souki
ABSTRACT The present case report describes the orthodontic treatment of a young adult patient (18y / 1m), Class III skeletal malocclusion, with mandibular prognathism and significant dental compensation. The canine relation was Class III, incisors with tendency to crossbite and open bite, moderate inferior crowding, and concave profile. Skeletal correction of malocclusion, facial profile harmony with satisfactory labial relationship, correction of tooth compensation and normal occlusal relationship were obtained with orthodontic treatment associated to orthognathic surgery. This case was presented to the Brazilian Board of Orthodontics and Facial Orthopedics (BBO), as part of the requirements to become a BBO diplomate.